Physical Activity: Patterns of active transport in 11-12 year old Australian children - Nathan Marten; Tim Olds (Elsevier, 2004)
Abstract Objectives: To describe the habitual transport patterns of 11 to 12‐year‐old children in Australia, to determine the personal and environmental factors associated with active transport (AT), and to quantify how much AT contributes to overall daily energy expenditure (EE). Methods: The participants in this study were 136 children aged 11-12 year olds from eight randomly chosen primary schools in Adelaide, South Australia. Each child recalled their trips on two school days and a non‐school day. Mass and stature were measured, and children completed a computerised activity recall and a neighbourhood satisfaction questionnaire. Trips were categorised according to their destination, child and parent dissatisfaction with the neighbourhood, and the gender, socio‐economic status (SES), BMI and activity levels of the children undertaking them. These categories, along with the distance to the destination, were used as independent variables in a logistic regression model, with trip mode (passive versus active) as the dependent variable. Results: Children made an average of 1.0 active trips per day, with a median trip length of 0.63 km, while the median total distance covered actively per child per day was 0.61 km. Twenty‐six per cent of children did no AT over the three days, and 67% did no AT on a weekend day. Distance was by far the strongest predictor of the likelihood that a trip would be active. Trips made by girls were less likely to be active compared with boys. Trips to the shops were less likely to be active than trips to school. Children's AT accounted for 1.3% of their daily EE. Conclusions and Implications: The active transport levels of children were very low. Interventions should focus on making neighbourhoods safer and more accessible to children and should promote bicycle use.